Case report: Novel compound heterozygous variants in the PANK2 gene in a Chinese patient diagnosed with ASD and ADHD - Dong, Siqi; Tuo, Ya; Qi, Zihan; Zhang, Yuanfeng; Liu, Xiaoni; Huang, Ping; Chen, Xiangjun (Frontiers in Neurology, 2023)
The PANK2 gene, which encodes mitochondrial pantothenate kinase 2 protein, is the disease-causing gene for pantothenate kinase-associated neurodegeneration (PKAN). We report a case of atypical PKAN with autism-like symptoms presenting with speech difficulties, psychiatric symptoms, and mild developmental retardation. Magnetic resonance imaging (MRI) of the brain showed the typical “eye-of-the-tiger” sign. Whole-exon sequencing revealed PANK2 p.Ile501Asn/p.Thr498Ser compound heterozygous variants. Our study highlights the phenotypic heterogeneity of PKAN, which can be confused with autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD) and requires careful clinical identification.